2016
DOI: 10.1515/epoly-2016-0217
|View full text |Cite
|
Sign up to set email alerts
|

Modification of pristine nanoclay and its application in wood-plastic composite

Abstract: The modification of pristine nanoclay and its application in wood plastic composite (WPC) have been investigated in this paper. Pristine nanoclay was modified using transition metal ion (TMI) which was copper (II) chloride to achieve good dispersion and to improve properties of WPC. The morphology, composition, structure, and thermal stability of TMI-modified nanoclay were studied by field emission scanning electron microscopy (FESEM), energy dispersive X-ray analysis (EDX), X-ray diffraction (XRD) and thermog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…This result is consistent with a wood-plastic composites study, in which the modification process reduced the size of nanoclay tactoids and resulted in better NP dispersion [38]. The decreased size of tactoids might be related to the ion exchange of Na + and Fe 2+ /Fe 3+ ions from the MMT lamellar structure [39]. Besides, the binding energies of the iron was detected at about 0.6, 6.3 and 7.0 keV [28] as shown by the EDX spectra.…”
Section: Discussionsupporting
confidence: 91%
“…This result is consistent with a wood-plastic composites study, in which the modification process reduced the size of nanoclay tactoids and resulted in better NP dispersion [38]. The decreased size of tactoids might be related to the ion exchange of Na + and Fe 2+ /Fe 3+ ions from the MMT lamellar structure [39]. Besides, the binding energies of the iron was detected at about 0.6, 6.3 and 7.0 keV [28] as shown by the EDX spectra.…”
Section: Discussionsupporting
confidence: 91%
“…Neat and modified montmorillonites (MMTs) generally have a wide variety of particle sizes 43 . It has been reported that after the modification process, the agglomerations in pristine MMT decreased and the NC agglomerates decreased in size 44 . The particle size distribution of unmodified and modified NCs is presented in Figure 3b,d, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…43 It has been reported that after the modification process, the agglomerations in pristine MMT decreased and the NC agglomerates decreased in size. 44 The particle size distribution of unmodified and modified NCs is presented in Figure 3b,d, respectively. It was found that the size of NC particles decreased after modification.…”
Section: Particle Size Distributionmentioning
confidence: 99%
“…Membranes 2023, 13, x FOR PEER REVIEW 11 of 17 persion. Therefore, for better compatibility and a homogenous dispersion, the clay surface needs to be modified using a cationic surfactant [36][37][38].…”
Section: Application Of Clay-based Nano Pigment For Colored Polymeric...mentioning
confidence: 99%